Public attitudes in England towards the sharing of personal data following a mass casualty incident: a cross-sectional study. Issue 5 (20th May 2018) - Rubin, G James; Webster, Rebecca; Rubin, Antonia N; Amlot, Richard; Grey, Nick; Greenberg, Neil
Abstract : Objectives: To assess public attitudes towards data sharing to facilitate a mental health screening programme for people caught up in a mass casualty incident. Design: Two, identical, cross-sectional, online surveys, using quotas to ensure demographic representativeness of people aged 18–65 years in England. Participants were randomly allocated to consider a scenario in which they witness a terrorism-related radiation incident or mass shooting, after which a police officer records their contact details. Setting: Participants were drawn from an online panel maintained by a market research company. Surveys were conducted before and immediately after a series of terrorist attacks and a large tower block fire occurred in England. Participants: One thousand people aged 18–65 years participated in each survey. Main outcome measures: Three questions asking participants if it would be acceptable for police to share their contact details, without asking first, with 'a health-related government organisation, so they can send you a questionnaire to find out if you might benefit from extra care or support', 'a specialist NHS team, to provide you with information about ways to get support for any physical or mental health issues' and 'your GP, so they can check how you are doing'. Results: A minority of participants reported that it would be definitely not acceptable for their details to be shared with the government organisation (n=259, 13.0%), the National Health Service (NHS) (n=141, 7.1%) and their general practitioner (GP) (n=166, 8.3%). There was a small, but significant increase in acceptability for the radiation incident compared with the mass shooting. No major differences were observed between the preincident and postincident surveys. Conclusions: Although most people believe it is acceptable for their details to be shared in order to facilitate a mental health response to a major incident, care must be taken to communicate with those affected about how their information will be used.